Effect of aerobic training status on both maximal lactate steady state and critical power - Greco, Camila Coelho [UNESP]; Correa Carita, Renato Aparecido [UNESP]; Dekerle, Jeanne; Denadai, Benedito Sergio [UNESP] (Canadian Science Publishing, Nrc Research Press, 2012)
This study aimed at assessing the sensitivity of both maximal lactate steady state (MLSS) and critical power (CP) in populations of different aerobic training status to ascertain whether CP is as sensitive as MLSS to a change in aerobic fitness. Seven untrained subjects (UT) (maximal oxygen uptake = 37.4 +/- 6.5 mL.kg(-1).min(-1)) and 7 endurance cyclists (T) (maximal oxygen uptake = 62.4 +/- 5.2 mL.kg(-1).min(-1)) performed an incremental test for maximal oxygen uptake estimation and several constant work rate tests for MLSS and CP determination. MLSS, whether expressed in mL.kg(-1).min(-1) (T: 51.8 +/- 5.7 vs. UT: 29.0 +/- 6.1) or % maximal oxygen uptake (T: 83.1 +/- 6.8 vs. UT: 77.1 +/- 4.5), was significantly higher in the T group. CP expressed in mL.kg(-1) .min(-1) (T: 56.8 +/- 5.1 vs. UT: 33.1 +/- 6.3) was significantly higher in the T group as well but no difference was found when expressed in % maximal oxygen uptake (T: 91.1 +/- 4.8 vs. UT: 88.3 +/- 3.6). Whether expressed in absolute or relative values, MLSS is sensitive to aerobic training status and a good measure of aerobic endurance. Conversely, the improvement in CP with years of training is proportional to those of maximal oxygen uptake. Thus, CP might be less sensitive than MLSS for depicting an enhancement in aerobic fitness.
Keywords: cycling; aerobic capacity; heavy-intensity domain; endurance